Pelatihan Perilaku Cerdik pada Kader Posbindu di Desa Candirejo, Kabupaten Semarang - Puji Purwaningsih; Heri Sugiarto; Zumrotul Chairijah; Izzatul Alifah Sifai; Nur Khasanah (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Changing in disease pattern is influenced by changes in the environment, community behaviour, demographic transition, technology, economy and socio-culture. This changing makes non-communicable diseases a strategic issue in the 2030 SDGs. This encourages promotive and preventive efforts by involving the community, namely cadres as the frontline in health. The theme of this health community service activity is to improve the knowledge and skills of cadres in the implementation of “Posbindu”. This activity was carried out from May 17th to June 11th, 2022 in Candirejo Village, Semarang Regency, followed by 9 people who are willing and including the requirements as cadres. This activity is counselling such as lectures and discussions. Smart behaviour practice activities at “Posbindu” are carried out according to the instructions of the Technical Instructions for Integrated Guidance for Cadre. The evaluation was carried out with a pre-post-test with the results that before giving this activity the average knowledge score of the participants was 1.89, after being given the activity, it was 11.22. This shows that there is an increasing knowledge score of 9.33. Public health service and village government always involve health cader in promoting society to have healthy life 2045.